Continuous Production of Ethylene and Hydrogen Peroxide from Paired Electrochemical Carbon Dioxide Reduction and Water Oxidation - Mavrikis, Sotirios; Nieuwoudt, Matthian; Göltz, Maximilian; Ehles, Sophie; Körner, Andreas; Hutzler, Andreas; Fossy, Emeric; Zervas, Andreas; Brai, Oshioriamhe; Wegener, Moritz; Doerrfuss, Florian; Bouwman, Peter; et al. (Advanced Energy Materials, 2024)
Paired electrolysis offers an auspicious strategy for the generation of high-value chemicals, at both the anode and cathode, in an integrated electrochemical reactor. Through efficient electron utilization, routine product misuse at overlooked electrodes can be prevented. Here, an original paired electrosynthetic system is reported that can convert CO2 to ethylene (C2H4) at the cathode, and water to hydrogen peroxide (H2O2) at the anode under a single pass of electric charge. Amongst various investigated copper (Cu) nanomorphologies, the bespoke mixed Cu nanowire/nanoparticle catalyst recorded a peak C2H4 Faraday efficiency (FE) of 60% following 370 h of electrolysis at 200 mA cm−2, while the tailored boron-doped diamond (BDD) anode accumulated an unprecedented ≈1% w/w of H2O2 in 4 m K2CO3 upon applying 300 mA cm−2 for 10 h. When paired, the dual C2H4-H2O2 electrochemical cell attains a combined FE of 120% for 50 h at 200 mA cm−2, a combined energy efficiency (EE) of 69%, and a 50% decrease in the overall electrical energy consumption (EEC) compared to the individual electrosynthesis of C2H4 and H2O2.
CRIS-Team Scopus Importer:2024-03-22
Keywords: CO; ethylene; hydrogen peroxide; paired electrolysis; water oxidation reaction (WOR)